Exploring the Typicality, Sensory Space, and Chemical Composition of Swedish Solaris Wines - Garrido-Bañuelos, Gonzalo (Foods, 2020)
The Swedish wine industry has exponentially grown in the last decade. However, Swedish wines remain largely unknown internationally. In this study, the typicality and sensory space of a set of twelve wines, including five Swedish Solaris wines, was evaluated blind by Swedish wine experts. The aim of the work was to evaluate whether the Swedish wine experts have a common concept of what a typical Solaris wines should smell and taste like or not and, also, to bring out more information about the sensory space and chemical composition of Solaris wines. The results showed a lack of agreement among the wine experts regarding the typicality of Solaris wines. This, together with the results from the sensory evaluation, could suggest the possibility of different wine styles for Solaris wines. From a chemical perspective, the global volatile profile showed a larger variability between individual wines than between Solaris and non-Solaris. However, 4MMP, ethyl propionate, ethyl 2-Methyl propanoate, and diethyl succinate were significantly higher in Solaris wines. Concerning non-volatile compounds, the results showed a significant discrimination between Solaris and non-Solaris wines, the former being characterized by higher ethanol %, Mg, succinic acid, tartaric acid, and sucrose levels.